Mechanisms of The Emergence of Resistance of Bacteria to Antibiotics, Methods of Combating Them in Medicine - Rustamova Diloro Mubinovna; Otabek Ashurov Shavkatovich (American Journal of Biology and Natural Sciences, 2025)
This article analyzes the nature of bacterial resistance to antibiotics and drugs, the mechanisms of its occurrence, its impact on human health and ways to prevent it. Resistance in bacterial populations is caused by improper antibiotic administration, genetic mutation of bacteria, antibiotic resistance, and adaptive properties. Complex mechanisms such as DNA-mediated gene transfer in plasmids, efflux pumps, help ensure the duration of the life activity of bacteria. The study of the emergence of an antibiotic resistance property serves as a basis in medicine to prevent and combat the incidence of pathogenic bacteria